Distribution och försäljning av kvalitetsfuru - Ståhl, Gustav (2007)
The purpose of this study is to analyse how a distribution and sale-network for quality softwood lumber should be designed to fit sawmilling companies' business concepts, and at the same time satisfy customer needs regarding delivery time and quality aspects. This thesis work is a case study based on a sawmilling and retail company in Sweden.